Nilai Ekonomis Penerapan Hazard Analysis Critical Control Point (HACCP) Terhadap Mutu Gizi Makanan: Systematic Literature Review Berbasis PRISMA Dan Bibliometrik - Hanun Kiyasah Izzah; Maheswari Cetta Wijaya; Islamiah Kamil (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze implementation costs, economic benefits, and the contribution of Hazard Analysis Critical Control Point (HACCP) to the protection of food nutritional quality based on scientific articles published from 2020 to 2026. The study used a Systematic Literature Review based on PRISMA 2020 and supported by simple bibliometric mapping. Articles were searched through Scopus, Web of Science, Google Scholar, Crossref/DOI, Garuda/Sinta, PubMed, ScienceDirect, MDPI, Frontiers, and relevant journal platforms. The results show that 17 articles discussed HACCP/FSMS, 7 articles focused on economic aspects and implementation barriers, and 6 articles examined nutritional quality and food processing. In addition, 20 articles or 66.7% were published in 2024-2025, indicating increased research attention to HACCP, FSMS, and digital food safety monitoring. The main costs of HACCP include training, documentation, equipment, audits, certification, and facility improvement, while the benefits include process efficiency, reduced product rejection, reputation improvement, and wider market access.